Faktor-faktor yang mempengaruhi Kualitas Laporan Keuangan: Sistem Informasi Akuntansi, Sistem Pengendalian Intern dan Kompetensi Sumber Daya Manusia - Dina Juniarti Barokah; Cris Kuntadi; Rachmat Pramukty (Jurnal Kendali Akuntansi, 2023)
This article reviews the factors that influence the quality of financial statements, namely accounting information systems, internal control systems and human resource competencies, a literature study on accounting information systems. The purpose of this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Accounting Information Systems affect the Quality of Financial Statements; 2) The Internal Control System affects the Quality of Financial Statements; and 3) Competence of Human Resources influences the Quality of Financial Statements.